Reductive Immobilization of Uranium(VI) by Amorphous Iron Sulfide - Hua, Bin; Deng, Baolin (Environmental science & technology, 2008)
Batch experiments were used to evaluate the reductive immobilization of hexavalent uranium (U(VI)) by synthesized, amorphous iron sulfide (FeS) in the anoxic environment. The tests were initiated by spiking 168.0 μM U(VI) to 0.18 g/L FeS suspensions under a CO2-free condition with pH varied from 5.99 to 10.17. The immobilization rate of U(VI) was determined by monitoring the changes of aqueous U(VI) concentration, and the reduction rate of U(VI) associated with FeS was determined by the difference between the total spiked U(VI) and the extractable amount of U(VI) by 25 mM NaHCO3 solution. The results showed that a rapid removal of U(VI) from the aqueous phase occurred within 1 h under all pH conditions accompanied by a simultaneous release of Fe(II), whereas the reduction of U(VI) associated with FeS took hours to over a week for completion. The reduction rate was greatly increased with decreasing pH within the examined pH range. Product analysis by X-ray photoelectron spectroscopy showed the formation of U3O8/U4O9/UO2, polysulfide, and ferric iron.